ETView VivaSight single lumen vs. conventional intubation in simulated studies: a systematic review and meta-analysis - Seok Kyeong Oh; Byung Gun Lim; Young Sung Kim; Jae Hak Lee; Young Ju Won (Journal of International Medical Research, 2020)
Objective The ETView VivaSight single lumen airway tube (ETView) is a tracheal tube incorporating a video camera. We carried out a meta-analysis of previous simulation studies by inexperienced personnel to determine if the ETView could improve the success rate of first-attempt intubation. Methods We collected data from randomized controlled trials comparing the use of the ETView VivaSight single lumen versus a conventional endotracheal tube in a simulated manikin or cadaver study. Results Eleven studies (558 participants, 3,254 intubations, and 19 scenarios) were included. The ETView had a significantly higher success rate and shorter insertion time than conventional intubation in both normal airways (with or without chest compression) and in difficult airways. In addition, the ETView demonstrated better results in terms of a higher rate of Cormack−Lehane grade 1 and a lower incidence of dental trauma. Conclusions Inexperienced personnel can insert the ETView more rapidly and with a higher intubation success rate compared with a conventional tube.